The yield of neuroimaging in patients presenting to the emergency department with isolated neuro-ophthalmological complaints: A retrospective chart review. Issue 4 (27th January 2023) - El Zahran, Tharwat; El Hadi, Dalia; Mostafa, Hala; Mansour, Hana; Hashim, Ibrahim; Tahhan, Soubhi; Bou Ghannam, Alaa
Abstract : Neuro-ophthalmological emergencies require prompt assessment and management to avoid vision or life-threatening sequelae. The decision to perform a neuroimaging procedure is based on the clinical judgment of the medical team, without defined indications. This study aims to identify presenting symptoms and physical exam findings associated with relative positive findings on neuroimaging studies. Electronic medical records of patients presenting to the emergency department (ED) with isolated neuro-ophthalmologic complaints between January 1, 2013 and September 30, 2019 were reviewed. We collected data on the clinical presentation, neuroimaging procedures and results, consults, and diagnoses. Two hundred eleven patients' charts were reviewed. Most presented with unilateral eye complaints (53.6%), and the most common symptoms were blurred vision (77.3%) and headaches (42.2%). A total of 126 imaging procedures were performed of which 74.6% were normal, while 25.4% showed relevant abnormal findings. Complaining of blurry vision ( P = .038) or visual field changes ( P = .014) at presentation as well as having a visual field defect ( P = .016), abnormal pupil reactivity ( P = .028), afferent pupillary defect ( P = .018), or abnormal optic disc exam ( P = .009) were associated with positive findings on imaging. Neuroimaging is more likely to yield positive findings in patients presenting to the ED with visual field irregularities, afferent pupillary defects, or abnormal optic discs. These findings – when combined with the proper clinical setting – should lower the threshold to proceed with neuroimaging in the emergency department. Based on our results, larger-scale studies might lead to a well-structured algorithm to be followed by ED physicians in decision making.